Latihan Fisik Aerobik Sebagai Upaya Pencegahan Gangguan Siklus Haid Pada Wanita Pre Menopouse - Octarina Piko, Sari; Zalila, Rifka; Elyta, Tuti; Martha, Rian; Saputri, Rika (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The purpose of this study is to determine how aerobic exercise impacts menstrual cycle disorders in premenopausal women. This study used a one-group pre-experimental pre-post-test method, where 20 respondents aged 40 to 50 participated in an aerobic exercise program 3 times a week for a month, or 12 sessions, each lasting 30 minutes, with an average attendance rate of 93%. Menstrual cycle regularity, duration of menstruation, intensity of menstrual pain, and volume of bleeding are all metrics that are measured. The research results show that all indicators experienced significant changes after the intervention. With a P value of 0.000 (p < 0.05), the menstrual cycle becomes more regular. The average cycle length was 29.5 ± 3.8 days, the duration of menstruation decreased to 5.9 ± 0.9 days, menstrual pain scores dropped drastically to 3.5 ± 1.1, and bleeding volume became more manageable at 3.2 ± 1.0 pads per day. Additionally, most respondents reported an improved quality of life; among other things, 80% experienced milder menstrual pain, 70% experienced emotional stability, and 60% felt more restful sleep. This study shows that aerobic exercise is effective as a non-pharmacological treatment for preventing and reducing menstrual cycle disorders in pre-menopausal women. This exercise also improves overall quality of life thru hormonal changes.